A new approach to inventorying bodies of water, from local to global scale - Bartout, Pascal; Touchart, Laurent; Terasmaa, Jaanus; Choffel, Quentin; Marzecova, Agata; Koff, Tiiu; Kapanen, Galina; Qsair, Zoubida; Maleval, Véronique; Millot, Camille; et al. (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Having reliable estimates of the number of water bodies on different geographical scales is of great importance to better understand biogeochemical cycles and to tackle the social issues related to the economic and cultural use of water bodies. However, limnological research suffers from a lack of reliable inventories; the available scientific references are predominately based on water bodies of natural origin, large in size and preferentially located in previously glaciated areas. Artificial, small and randomly distributed water bodies, especially ponds, are usually not inventoried. Following Wetzel’s theory (1990), some authors included them in global inventories by using remote sensing or mathematical extrapolation, but fieldwork on the ground has been done on a very limited amount of territory. These studies have resulted in an explosive increase in the estimated number of water bodies, going from 8.44 million lakes (Meybeck 1995) to 3.5 billion water bodies (Downing 2010). These numbers raise several questions, especially about the methodology used for counting small-sized water bodies and the methodological treatment of spatial variables. In this study, we use inventories of water bodies for Sweden, Finland, Estonia and France to show incoherencies generated by the “global to local” approach. We demonstrate that one universal relationship does not suffice for generating the regional or global inventories of water bodies because local conditions vary greatly from one region to another and cannot be offset adequately by each other. The current paradigm for global estimates of water bodies in limnology, which is based on one representative model applied to different territories, does not produce sufficiently exact global inventories. The step-wise progression from the local to the global scale requires the development of many regional equations based on fieldwork; a specific equation that adequately reflects the actual relationship between distribution and abundance of water bodies in a given area must be produced for each geographical region.